HIV TAT-mediated microglial senescence: Role of SIRT3-dependent mitochondrial oxidative stress - Annadurai Thangaraj; Ernest T. Chivero; Ashutosh Tripathi; Seema Singh; Fang Niu; Ming-Lei Guo; Prakash Pillai; Palsamy Periyasamy; Shilpa Buch (Redox Biology, 2021)
The advent of combined antiretroviral treatment (cART) as a treatment for HIV-1 infection has not only resulted in a dramatic decrease in the peripheral viral load but has also led to increased life expectancy of the infected individuals. Paradoxically, increased lifespan is accompanied with higher prevalence of age-related comorbidities, including HIV-associated neurocognitive disorders (HAND). Present study was aimed at exploring the role of HIV TAT protein in mediating microglial mitochondrial oxidative stress, ultimately resulting in neuroinflammation and microglial senescence. Our findings demonstrated that exposure of mouse primary microglial cells (mPMs) to HIV TAT protein resulted in a senescence-like phenotype, that was characterized by elevated expression of both p16 and p21 proteins, increased numbers of senescence-associated-β-galactosidase positive cells, augmented cell-cycle arrest, increased release of proinflammatory cytokines and decreased telomerase activity. Additionally, exposure of mPMs to HIV TAT also resulted downregulation of SIRT3 with a concomitant increase in mitochondrial oxidative stress. Dual luciferase reporter assay identified miR-505 as a novel target of SIRT3, which was upregulated in mPMs exposed to HIV TAT. Furthermore, transient transfection of mPMs with either the SIRT3 plasmid or miRNA-505 inhibitor upregulated the expression of SIRT3 and mitochondrial antioxidant enzymes, with a concomitant decrease in microglial senescence. These in vitro findings were also validated in the prefrontal cortices and striatum of HIV transgenic rats as well as cART-treated HIV-infected individuals. In summary, this study underscores a yet undiscovered novel mechanism(s) underlying HIV TAT-mediated induction of senescence phenotype in microglia, involving the miR-505-SIRT3 axis-mediated induction of mitochondrial oxidative stress.